Possibly Ill-behaved Posteriors in Econometric Models - Lennart Hoogerheide; Herman K. van Dijk (Tinbergen Institute, 2008)
Highly non-elliptical posterior distributions may occur in several econometric models, in particular, when the likelihood information is allowed to dominate and data information is weak. We explain the issue of highly non-elliptical posteriors in a model for the effect of education on income using data from the well-known Angrist and Krueger (1991) study and discuss how a so-called Information Matrix or Jeffreys' prior may be used as a `regularization prior' that in combination with the likelihood yields posteriors with desirable properties. We further consider an 8-dimensional bimodal posterior distribution in a 2-regime mixture model for the real US GNP growth. In order to perform a Bayesian posterior analysis using indirect sampling methods in these models, one has to find a good candidate density. In a recent paper - Hoogerheide, Kaashoek and Van Dijk (2007) - a class of neural network functions was introduced as candidate densities in case of non-elliptical posteriors. In the present paper, the connection between canonical model structures, non-elliptical credible sets, and more sophisticated neural network simulation techniques is explored. In all examples considered in this paper – a bimodal distribution of Gelman and Meng (1991) and posteriors in IV and mixture models - the mixture of Student's t distributions is clearly a much better candidate than a Student's t candidate, yielding far more precise estimates of posterior means after the same amount of computing time, whereas the Student's t candidate almost completely misses substantial parts of the parameter space.
Keywords: C11; C15; C45; 330; instrumental variables; vector error correction model; mixture model; importance sampling; Markov chain Monte Carlo; neural network; Instrumentalvariablen-Schätzmethode; Fehlerkorrekturmodell; Statistisches Auswahlverfahren; Markovscher Prozess; Monte-Carlo-Methode; Neuronale Netze; Simulation; Theorie